ATOMIZED SOCIETY: The Role OF Women And Social Media IN Cultivating Multipolar Outcome of Globalization - Mursyidi, Ach Fatayillah (PALASTREN: Jurnal Studi Gender, 2019)
Globalization has been so far understood as a mere global phenomenon that benefits all group of people while its negative effects are commonly ignored. This paper examines multipolar outcome of globalization in which women and social media are mostly taking a part. I am focusing only on women’s role as the dominant users of internet without, of course, overlooking intentionally men’s role. To build my argument, I started this paper by arguing that the idea of ‘imagined community’ by Benedict Anderson and ‘conversed community’ by Merlyna Lim are no longer sufficient to portray the impact on social condition nowadays. Rather than using those terms, I proposed another term which is more appropriate to apply; it is atomized society. In this regard, the role of both women and social media are very significant in paving a way of atomized society. Finally, through an informal interview I conducted with some members of LISMA (Lingkar Studi Mahasiswi Muslim Peduli Negeri), a faith-based women community in Yogyakarta, it exemplifies how women are evidently vulnerable to such global effect with the help of social media.